PEMBERIAN HADIAH IKOY-IKOYAN DITINJAU DARI PERSPEKTIF FIQH MUAMALAH - Tia Ifanka; Syofia Ulfah; Rahmat Hidayat Hidayat (Saqifah: Jurnal Hukum Ekonomi Syariah, 2023)
The word ikoy-ikoyan is not found in KBBI or Wikipedia because ikoy-ikoyan is a new vocabulary is that present on instagram. Ikoy-ikoyan is a sharing mode that was first introduced by an Indonesian celebgram named Arief Muhammad, with his real name Muhammad Arief  Yakoeb. This research is important examine so that in giving ikoy-ikoyan gifts on instagram and implementing muamalah it does notviolate the provisions that have been regulated or recommended by the Shari’a. This study uses a qualitative methods. Primary data was obtained from documentation in the form of screenshots from accounts carrying out ikoy-ikoyan on Instagram. Secondary data was obtained from interviews with those who first held the ikoy-ikoyan. The data obtained is processed using the content analysis method. The research resulted in the following conclusion, the fiqh muamalah analysis of giving ikoy-ikoyan gifts on Instagram is permissible (permissible) as long as there is no argument stating that it is forbidden. Regarding their permissibility, ikoy-ikoyan have pillars and conditions that make the law valid. In giving ikoy-ikoyan gifts there are no conditions that are burdensome to the recipient and none of the conditions given conflict with the conditions for the validity of a gift.